(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article deals with an important issues as the reference of proper names and their actualization in the space of a literary text. Of particular interest from this point of view is the functioning of precedent proper names in a lyrical work, since in this case the precedent name becomes the semantic dominant of the text, influencing the formation of both content and meaning. They contain a large corpus of various proper names, these are mainly precedent names, each of them has its own text, also precedent, which, when included in a new context, acquires a new meaning, requiring a new reading.